Housing Price Index, Wealth, and Protective Shield against Covid-19 - Mihai Pichler; Florin Skutnik; Aurel Vlad; Hossein Shahri; Muhammad Ridwan (SIASAT, 2021)
This paper aims to fill two purposes: 1) we document that housing price index between different cities have inter-correlation. This means that when the housing price in one city goes up the other city follows. However, in the case of a big city and a small city, the housing price index of small city follows the path of housing price index in the small city. 2) The housing price index is a measure of wellbeing and wealth of residents. At the onset of a pandemic, wealthy and richer people have a wealth-protective shield against the disease. We show that this is the case in the US. We document that higher housing price indexes are associated with lower confirmed case of Covid-19 and lower risks of death due to the disease.